Fungi and earthworm abundance and diversity as affected by biochar and mulching amendments in ethiopian mustard production - Naza Emanuel Mmbaga; Stanslaus Terengia Materu (PLoS ONE, 2026)
Organic agriculture relies on the in-field generation of nutrients through the decomposition and mineralization of organic matter (OM). Soil macro- and micro-organisms are vital for this self-sustaining nutrient production; however, insufficient organic matter, limited microorganisms, and poor soil conditions can impede the process. This study investigated the effects of biochar and mulching on the abundance and diversity of soil microorganisms (fungi) and macro-organisms (earthworms) under Ethiopian mustard ( Brassica carinata ) cultivation over two growing seasons in 2023. The site featured loamy soil with a pH of 5.5–6.0. Treatments included rice husks biochar (5 t/ha); rice husk mulching and compared to a control, using a completely randomized block design with three replicates. Measurements included fungal colony abundance, earthworm frequency, Simpson diversity index, and soil moisture retention under rainfed conditions with minimal irrigation during dry spells. Results showed that at a 5 cm soil depth, biochar increased fungal abundance by 32.05% compared to mulching, and by 113.35% relative to the control. Mulching also improved colony abundance by 61.57% over the control. At a depth of 10 cm, biochar enhanced colony abundance by 42.14% compared to mulching and by 42.82% relative to the control. The highest diversity index (0.596) was observed in biochar-treated blocks, while the control had the lowest (0.422). Earthworms were the most abundant macro-organisms in both treatments. Biochar’s characteristics may help recondition poor, acidic soils, improving conditions for macro and micro-organisms, thereby enhancing soil health and productivity. These microbial improvements could benefit not only Ethiopian mustard but also major cereal cropping systems. Biochar consistently increased fungal abundance and earthworm frequency across both season.